In search of Meaning: The Written Word in the Age of Google - Anita Paz (JLIS.it, 2013)
The article intends to be a short theoretical elaboration of the ideas raised by Boris Groys in Google: Words beyond Grammar from a LIS point of view. Through the use of critical tools such as Manovich's theory of the database and Wittgenstein's writings on meaning and context, the author delineates a double partial characteristic of the search conducted by Google in terms of quality (the Google algorithm is partial towards results claimed to appertain the user's interests) and in terms of quantity (the Google interface will only allow the user partial access to the search results).